Komunikasi Interpersonal melalui Layanan Bimbingan Kelompok di STAI Ma'arif Jambi - Yulianti Yulianti; Ria Hayati (Prodi Bimbingan dan Konseling Islam, 2021)
This study aims to determine the application of group guidance services to develop colage student interpersonal communication in STAI MAARIF JAMBI study program BKPI. The research method used is descriptive qualitative. Data obtained from interviews, observations and documentation sourced from students of the BKPI Study Program STAI MAARIF JAMBI. The collected data is followed up with data reduction, data display and drawing conclusions. Group guidance service is one of the services that exist in counseling guidance services, where group guidance services aim to train students to dare to express their opinions, train to convey solutions, practice critical thinking. Group guidance services are expected to be able to improve students' skills in good communication.